2020
DOI: 10.1155/2020/4039140
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Perinatal Outcomes of Singleton Term Breech Vaginal Delivery at a Tertiary Care Center in Nepal: A Retrospective Analysis

Abstract: Background. Breech presentation is associated with increased rates of maternal and perinatal morbidity regardless of mode of delivery. After the results of Term Breech Trial, most of the countries adopted the protocol of cesarean section for term breech delivery because of which breech vaginal delivery is becoming rare. The aim of this study is to evaluate short-term maternal and perinatal outcomes of breech vaginal delivery at a tertiary care hospital in Nepal. Methods. A retrospective review of case records … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 22 publications
1
5
3
Order By: Relevance
“…This study was aimed at determining the prevalence and perinatal outcomes of singleton breech delivery at a tertiary level hospital in Nepal. The prevalence of breech presentation in our study was higher than that reported by previous studies conducted in Nepal (1.9-3.1%), 10,13,14 but it was less than the prevalence reported in Ethiopia 5 and Malaysia. 6 Our centre is a tertiary level hospital where significantly large number of cases of high-risk pregnancy including abnormal presentations are referred in, which might be the reason for higher incidence of breech in comparison to previous national studies.…”
Section: Discussioncontrasting
confidence: 85%
See 3 more Smart Citations
“…This study was aimed at determining the prevalence and perinatal outcomes of singleton breech delivery at a tertiary level hospital in Nepal. The prevalence of breech presentation in our study was higher than that reported by previous studies conducted in Nepal (1.9-3.1%), 10,13,14 but it was less than the prevalence reported in Ethiopia 5 and Malaysia. 6 Our centre is a tertiary level hospital where significantly large number of cases of high-risk pregnancy including abnormal presentations are referred in, which might be the reason for higher incidence of breech in comparison to previous national studies.…”
Section: Discussioncontrasting
confidence: 85%
“…A recent study on breech presentation had reported a prevalence of 2.4% in Nepal. 10 Considering the same prevalence as our expected frequency and with 95% confidence level and 2% margin of error; sample size was calculated to be 225 from openepi.com, open source software for epidemiologic statistics. However, 226 pregnant women were enrolled in the study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…There was a view that vertex-breech presentation was attributed to an earlier gestational age. An alternative view was that breech presentation caused uterine overdistention, leading to premature rupture of membranes [29].…”
Section: Discussionmentioning
confidence: 99%